Between Statehood and Somalia: Reflections of Somaliland Statehood - Dimitrios Lalos (Washington University Global Studies Law Review, 2011)
The Article presents information on the statehood of Somalia with respect to the international law and the rule of law under the Supreme Court of Canada. The independence of Somalia brought both the British Somaliland and the Italian Somaliland under Somali Republic and resulted in the emergence of the Somaliland as a de facto state. Information on the historical and economical traditions of the Somali Republic and the Republic of Somaliland is also presented.
Keywords: International law; Rule of law; British Somaliland -- History; Canada. Supreme Court